What do Social Processes mean for Quality of Human Resource Practice? - Nielsen, Kjeld; Pedersen, Louise Møller (Nordic Journal of Working Life Studies, 2014)
Well implemented human resource practice (HRP) is linked to increased performance, innovation, and the well-being of both managers and employees. In the literature, a distinction between the hard and the soft HRM-models is drawn: the hard model focuses on employees as a cost, whereas the soft HRM-model treats them as a potential Nielsen (2008a). However, little is known about the informal aspects of HRP and which social processes actually lead to implementation success or failure. The purpose of this paper is to develop a concept of social processes between managers and employees that can increase the implementation and quality of HR-performance Two studies of HRP within two manufacturing companies are used to illustrate the pros and cons of this new theoretical concept from a performance perspective. Involvement, commitment, and competence development are identified as key aspects of the quality of HRP. Moreover, a good psychological working environment and systematic priority of HRP are essential contextual factors that can enable or hinder social processes. Otherwise, production pressure and power relations between managers and employees can hinder the implementation of the new concept. The concept of social processes can help HRP to contribute on social processes between managers and employees as important aspects of quality in work with human resources. However, the influence of team organization and the social processes between employees needs to be explored further.